The effect of enzymatic hydrolysis on the biological properties of Oenothera biennis, Borago officinalis and Nigella sativa seedcake by‐products from oil pressing. (31st January 2014) - Ratz‐Łyko, Anna; Arct, Jacek; Herman, Anna; Pytkowska, Katarzyna; Majewski, Sławomir
Summary The biological properties of ethanolic (50%, v/v) extracts from Oenothera biennis, Borago officinalis, Nigella sativa seedcake before and after enzymatic hydrolysis by alpha‐amylase (EC 3.2.1.1) from Aspergillus oryzae, beta‐glucosidase (EC 3.2.1.21) and beta‐glucanase (EC 3.2.1.6) from Aspergillus niger combinations in a ratio of 1:1:1 were investigated. Total phenolic, flavonoid and reducing sugar content for O. biennis extract after enzymatic hydrolysis was, respectively, 0.5, 1.5 and 2 times higher in comparison with nonhydrolysed extract. Iron‐chelating and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghmgm7pv0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />O2−</alternatives> radical‐scavenging activity of O. biennis seedcake extract after hydrolysis (IC50 = 0.076 mg mL−1 and IC50<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghmgm7pwh" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />O2−</alternatives> = 0.050 mg mL−1) was at a similar level as that nonhydrolyeed (IC50 = 0.070 mg mL−1 and IC50<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghmgm7pfs" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />O2−</alternatives> = 0.065 mg mL−1). The antioxidant activity was two times higher after hydrolysis than before enzymatic hydrolysis of O. biennis seedcake extract. Also strong elastase inhibition activity has been shown to O. biennis seedcake extract before (IC50 = 0.095 mg mL−1) and after enzymatic hydrolysis (IC50 = 0.07 mg mL−1), respectively. Oenothera biennis and B. officinalis seedcake extracts before and after hydrolysis have stronger antibacterial activity against Pseudomonas aeruginosa strain in comparison with N. sativa seedcake.